Impacts Of Teacher Talk On Students’ Interaction In Efl Classroom - Haniyah, Rana; Sri, Melisa; Marlina, Neni (Universitas Siliwangi, 2024)
This research paper was intended to investigate the impacts of teacher talk on students’ interaction in one of the Junior High School in Tasikmalaya. Classroom research is chosen to investigate a classroom phenomenon about impacts of teacher talk on students’ participation in teaching and learning process. This research involves thirty two students. Four students and an English teacher become to be interviewed. The data collection used is observation and semi-structured interview then the data analyzed thematically. The result shows that teacher talk can make students actively communicate and involve in teaching learning process. Through the teacher talk, questions and instructions, the students are led to give responses to share their ideas and follow the instructions to achieve learning objectives. Hence, they can have classroom interaction which supports them in the learning process.